Establishing whether the structural feature controlling the mechanical properties of starch films is molecular or crystalline. (6th March 2015) - Li, Ming; Xie, Fengwei; Hasjim, Jovin; Witt, Torsten; Halley, Peter J.; Gilbert, Robert G.
Highlights: Thermoplastic starches (TPS) are "green" but mechanical properties are often poor. The properties of TPSs were related with varied molecular and crystalline structures induced by extrusion. Crystalline structure had the greatest effect. Mechanisms of property enhancement were explored. Amylopectin degradation induced by extrusion did not affect mechanical properties. Abstract: The effects of molecular and crystalline structures on the tensile mechanical properties of thermoplastic starch (TPS) films from waxy, normal, and high-amylose maize were investigated. Starch structural variations were obtained through extrusion and hydrothermal treatment (HTT). The molecular and crystalline structures were characterized using size-exclusion chromatography and X-ray diffractometry, respectively. TPS from high-amylose maize showed higher elongation at break and tensile strength than those from normal maize and waxy maize starches when processed with 40% plasticizer. Within the same amylose content, the mechanical properties were not affected by amylopectin molecular size or the crystallinity of TPS prior to HTT. This lack of correlation between the molecular size, crystallinity and mechanical properties may be due to the dominant effect of the plasticizer on the mechanical properties. Further crystallization of normal maize TPS by HTT increased the tensile strength and Young's modulus, while decreasing the elongation at break. The results suggest that the crystallinity from the remaining ungelatinized starch granules has less significant effect on the mechanical properties than that resulting from starch recrystallization, possibly due to a stronger network from leached-out amylose surrounding the remaining starch granules.